THEORY AND PRACTICE OF TRANSLATION - Nazirova Diyoraxon; Ahmedov Azimjon (TADQIQOTLAR, 2025)
Thesis Summary: Translation is the process of transferring meaning from one language to another while preserving the original message, tone, and cultural context. The  theory  of  translation  focuses  on  the  principles  and  strategies  used  to  achieve accurate and meaningful translations. It includes key concepts such as equivalence, fidelity, adaptation, and the role of the translator. Translation theories are often divided into literal (word-for-word) and free (sense-for-sense) approaches. In  practice,  translators  must  consider  various  factors,  including  linguistic structure, cultural differences, and contextual meaning. The practice of translation is more than just converting words; it involves deep understanding of both source and target  languages,  as  well  as  their  cultures.  Practical  challenges  include  idioms, proverbs, humor, technical terms, and untranslatable concepts. Successful translation depends on the translator's skills, knowledge, and ethical responsibility. It is both a science and an art, requiring analytical thinking and creative problem-solving.  Today,  the  use  of  technology,  such  as  CAT  tools  and  machine translation, also plays a significant role in modern translation practice. In conclusion, the theory provides a foundation for understanding translation principles, while practice demonstrates how these principles are applied in real-world situations. Both aspects are essential for effective and professional translation.